Inventory of Moss Plants (Bryophyta) in the Montana Zone, Samiran Village, Selo District, Boyolali Regency, Central Java Province - Wardani, Eva Diahayu; Santhyami, S (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Green plants known as moss plants (Bryophyta) are considered low plants. Mosses can dwell in tropical regions, the highlands, and the lowlands, and some species even live in water. Temperature, humidity, living conditions, light intensity, habitat pH, substrate, and altitude are all known to have an impact on moss growth. At a height of 1,500–2,400 meters, in the montana zone, the diversity of species declines. Samiran Village, Selo District, Boyolali Regency, Central Java Province is one of the locations in the montana zone. Numerous variables in this location contribute to the habitat for moss growth. This study aims to ascertain the diversity and distribution of moss plants (Bryophyta) in the montana zone, Samiran Village, Selo District, Boyolali District, Central Java Province. There has never been researching on the inventory of moss plants in the montana zone of Samiran Village, Selo District. The study's findings revealed three divisions, Bryopsida, Hepacopsida, and Anthoceropsida, which were further divided into seven families, Marchantiaceae, Hypnaceae, Pottiaceae, Polytrichaceae, Lejeuneaceae, and Anytoniaceae. At an elevation of 1600–1800 meters above sea level, in the montana zone of Samiran Village, Selo District, Boyolali Regency, Central Java Province, the index value of moss plant diversity is 1.679, which is categorized as moderate. This is so because the study site functions well as a moss plant habitat.